Non-Muslim consumers' perception toward purchasing halal food products in Malaysia. (9th March 2015) - Haque, Ahasanul; Sarwar, Abdullah; Yasmin, Farzana; Tarofder, Arun Kumar; Hossain, Mirza Ahsanul
Abstract : Purpose: – This study aims to identify the factors that influence Malaysian non-Muslim consumers' perception towards buying halal food products. Design/methodology/approach: – A structured close-ended questionnaire was used for data collection through a random distribution to 500 non-Muslim consumers from various states in Malaysia. Findings: – Using SPSS package, the factor analysis was able to identify three main variables. Later, the hypotheses were tested using structural equation modelling. This study has indicated that the perception of non-Muslim consumers about halal food products is influenced by their attitude, subjective norm and perceived behavioural control, specifically in the context of Malaysia. Research limitations/implications: – This finding will help both the academics and the industry food makers in understanding the perception of non-Muslim consumers towards the concept of halal food products. Practical implications: – The outcome of the study can serve as a useful reference to relevant Malaysian statutory bodies on the current perception of the Malaysian non-Muslim consumers towards Malaysian halal agenda. This will also help the industry food makers to serve their customers better as well as maximize their profit through a well-planned marketing campaign. Social implications: – It prepares a sound basis for Malaysian policymakers to promote the involvement of Malaysian non-Muslim entrepreneurs within the halal food service industry with the intent of improving the socio-economic strata of its participants and, at the same time, fulfilling their religious obligations in providing halal foods for fellow Muslims. Originality/value: – Because very few researches have studied non-Muslim consumers' perception towards halal food products, the development of halal food theory will help in capitalizing the practices in non-Muslim countries.